2014
DOI: 10.4161/temp.29719
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of heat acclimation from hypoxic damage in the brain involves changes in the expression of glutamate receptors

Abstract: Long-term heat acclimation (34 °C, 30d) alters the physiological responses and the metabolic state of organisms. It also improves ability to cope with hypoxic stress via a cross-tolerance mechanism. Within the brain, the hippocampal and frontal cortex neurons are the most sensitive to hypoxia and cell death is mainly caused by calcium influx via glutamate-gated ion channels, specifically NMDA and AMPA receptors. GluN1 subunit levels of NMDA-R correspond to NMDA-R levels. GluN2B/GluN2A subunit ratio is a qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…There was a long gap between the 1955 study of Hiestand et al (66) where mice acclimated for 14 days survived anoxia better than the nonacclimated ones and 1993 when data on heat acclimation mediated cross-tolerance began to accumulate (119). We have evidence that heat acclimation induces cross tolerance against several environmental stressors associated with oxygen supply-oxygen demand mismatching such as ischemia/reperfusion, hypoxia (64,77,119,242) hyperoxia (4,42) ionizing radiation (176) TBI (211), and noise induced hearing loss (167).…”
Section: Heat Acclimation Mediated Cross-tolerancementioning
confidence: 99%
“…There was a long gap between the 1955 study of Hiestand et al (66) where mice acclimated for 14 days survived anoxia better than the nonacclimated ones and 1993 when data on heat acclimation mediated cross-tolerance began to accumulate (119). We have evidence that heat acclimation induces cross tolerance against several environmental stressors associated with oxygen supply-oxygen demand mismatching such as ischemia/reperfusion, hypoxia (64,77,119,242) hyperoxia (4,42) ionizing radiation (176) TBI (211), and noise induced hearing loss (167).…”
Section: Heat Acclimation Mediated Cross-tolerancementioning
confidence: 99%
“…) and reduces neuronal damage and cognitive deficits following cerebral hypoxia‐reoxygenation (H/R) (Yacobi et al . ). In humans, we showed that acute hot water immersion protects against reductions in brachial artery endothelial function induced by whole‐arm ischaemia‐reperfusion (Brunt et al .…”
Section: Introductionmentioning
confidence: 97%
“…Yacobi et al . () also demonstrated the importance of glutamate receptors during hypoxic insults, which facilitate neuronal death via calcium penetration following a large glutamate surge. In this study, long term (30 days), but not short term (2 days), heat‐acclimated rats exhibited lower presence of NMDA GluN1 proteins (i.e.…”
mentioning
confidence: 92%
“…lower receptor density) and reduced calcium permeability, highlighting different mechanisms by which heat acclimation‐induced hypoxia cross‐tolerance confers neuroprotection (Yacobi et al . ). Importantly, these results translated into improved functional outcomes of behaviour assessment in the 30‐day heat‐acclimated rats following hypoxia, indicating preserved cognitive function (Yacobi et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation